MOLECULAR CHARACTERIZATION OF THYMUS SPECIES USING ISSR MARKERS - V. Yousefi; A. Najaphy; A. Zebarjadi; H. Safari (Journal of Animal and Plant Sciences, 2015)
Thyme (Thymus spp.), a famous herb from Lamiaceae/Labiateae family is a valuable medicinal plant. In this study, fourteen accessions of Thymus species including T. daenensis, T. kotschyanus and T. vulgaris have been genetically fingerprinted by Inter simple sequence repeat (ISSR) markers. The 20 ISSR primers amplified 334 fragments, of which 325 were polymorphic. Number of amplified fragments ranged from 4 to 30 and their size was 200-2800 bps. Effective multiplex ratio (EMR) had wide-ranging data from 4 to 30 with an average of 15.84. Polymorphism information content (PIC) data were between 0.33 and 0.49. The mean of marker Index (MI) and resolving power (RP) were 6.63 and 10.64, respectively. The ISSR genotyping data were used to evaluate genetic diversity and the relationships among the accessions using UPGMA cluster analysis and principal coordinate analysis (PCoA). Both of the methods classified the 14 Thymus accessions in five sets and presented analogous grouping of the genotypes with some minor differences. The accessions were relatively grouped according to the location where they were collected. The analyzed ISSR markers created sufficient polymorphism and reproducible fingerprinting profiles and provided a powerful and reliable molecular tool for detecting genetic variation and relationships.
Keywords: genetic diversity; genetic polymorphism; ISSR; marker parameters; medicinal plant; Thymus